Maternal Depression and Its Association with Various Aspects of Early Childhood Development in Indonesia: A Multidimensional Review - Josafat, Gantha; Setiasari, Febi Jian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
One prevalent mood illness in the prenatal period that has a significant impact on the quality of early childhood development is maternal depression. Due to socioeconomic position, a lack of social support, and restricted access to healthcare facilities, this condition in Indonesia develops into a complicated public health concern. This study aims to comprehensively review the association between maternal depression and the cognitive, emotional, social, and physical development of children within the local Indonesian context. This article was composed through a systematic review of nine relevant primary scientific articles. A literature search was conducted on the PubMed, NCBI, Elsevier, and Google Scholar databases using relevant keywords. The review indicates that maternal depression negatively impacts various domains of child development. Cognitively, children of mothers with high-stress levels tend to experience difficulties with focus and concentration. In the socio-emotional domain, these children show difficulties in emotion regulation and tend to withdraw from social interaction. Physically, maternal depression was found to have a positive correlation with an increased risk of stunting in children. This impact is reinforced by contextual factors in Indonesia, such as the scarcity of maternal mental health services, minimal screening, and social stigma that prevents mothers from seeking help. The conclusion is that maternal depression is a serious health issue in Indonesia with multidimensional impacts on child development. Integrated efforts are needed, including routine screening, capacity building for health workers, and culturally sensitive interventions to reduce the burden of maternal depression and prevent its long-term effects on children.